CONCERNING THE WAY OF DIAGNOSTICS AND CORRECTION OF DYSBIOSIS BASED ON COMPLEX IMMUNO-MICROBIOLOGICAL ANALYSIS - L. V. Serdyuk; S. M. Popkova; E. B. Rakova; U. M. Nemchenko; M. V. Savelkaeva; S. I. Leshchuk; E. L. Kichigina; G. V. Yurinova (Acta Biomedica Scientifica, 2014)
The article presents theoretical ground of the method of correction of intestinal dysbiosis based on a complex immuno-microbiological examination combining research of quantitative and qualitative composition of intestinal microbiota with study of immune reactivity of an organism to bifidus bacteria. As a part of the task we performed bacteriological and serological analysis of 314 coprofiltrate samples of 1-14 years old children living in Irkutsk. On the basis of the studied materials we presented the algorithm of complex study with the ground of possible ways of correction of dysbiotic disorders.